(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian Women start writing in English extremely late which is one and fifty years old. Britishers should India for 200 years. India and England had dealt with each other in trade Military and Political affairs from Chronicled point of view, Indian English literature has gone through a few stages for example, Indo-Anglian, Idno-English, Indian writing in English and as of late Indian English writing. As a result it has aroused a good deal of interest for Indian women author. The works of various women writing get not only vast category of readers, but also receive a vast critical acclaim.